Optimizing Government Internal Audits through the Implementation of Blockchain Technology for Fraud Prevention - Rahman, Karlina Ghazalah; Rachma, Nur (LifeSciFi, 2025)
Fraud in public financial management remains a major challenge in developing countries like Indonesia, where weak internal controls and low transparency facilitate corruption, data manipulation, and budget misuse. This study examines the influence of government internal audits on fraud prevention and the role of blockchain technology in enhancing audit effectiveness within the Barru Regency government. A quantitative approach was employed, with data collected via questionnaires from 70 respondents across seven purposively selected government agencies. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) through SmartPLS 4. The results indicate that internal audits positively and significantly impact fraud prevention, and blockchain technology also contributes significantly to reducing fraud. However, the moderating effect of blockchain on the relationship between internal audits and fraud prevention was found to be insignificant, suggesting that current blockchain adoption does not enhance audit effectiveness. The model explains 83.5% of the variance in fraud prevention, demonstrating strong predictive power. These findings highlight that while internal audits and blockchain independently support fraud prevention, effective integration requires comprehensive digital transformation, supported by political commitment, clear regulations, and capacity building, to fully realize blockchain’s potential in strengthening public sector governance.